THE INFLUENCE OF BRAND IMAGE AND PRICE PERCEPTION ON NIVEA PRODUCT PURCHASE DECISIONS (CASE STUDY AT SMAN I PINTU POHAN MERANTI) - Wenny Widiyawati Simangunsong; Yuni Syahputri (RADJA PUBLIKA, 2025)
This study aims to determine the effect of Brand Image, Price Perception on the decision to purchase Nivea products on students of SMA Negeri 1 Pintu Pohan Meranti. The sampling technique used in this study is non-probability sampling, namely purposive sampling and the number of samples in this study is 96 consumers who purchased Nivea products. The data analysis technique used is descriptive analysis technique and statistical analysis technique. The method of data collection through distribution, namely conducting searches and distributing questionnaires to consumers of Nivea products. The results of this study indicate that partially the Brand Image variable (X1) has a positive and significant effect on the decision to purchase Nivea at SMAN 1 Pintu Pohan Meranti (Y). Partially the price perception variable (X2) has a positive and significant effect on the decision to purchase Nivea at SMAN 1 Pintu Pohan Meranti (Y). Simultaneously there is a positive and significant influence on the Brand Image variable (X1) and price perception (X2) on the decision to purchase Nivea at SMAN 1 Pintu Pohan Meranti (Y).